The Use of PJBL Method in Improving Students' Writing Ability in the English for Ecotourism Course - Firmansyah, Firman Syah; Yetty; Nadia Idris; Alifia Nur Aisyah; Fatimah (Institut Agama Islam Negeri Palopo, 2025)
Project Based Learning (PjBL) method can be as an alternative that might be used to solve problems in learning writing. This research aims to investigate whether the use of the PjBL method can help students in improving their ability and creativity in writing descriptive texts and explore the students’ perceptions regarding the implementation of Project Based Learning (PjBL) method in writing. This research was conducted at FKIP Khairun University. The data sources as subjects in this research were 21 students in the English Language Education Study Program who were currently implementing courses English for Ecotourism. This research is pre-experimental research with quantitative research methods. Data collection methods were pre-test, post-test and using questionnaires. The results of this study show that there is a significant difference between the pre-test and post-test scores. The average score on the pre-test was 57.10 and the average score on the post-test was 84.95. T- calculated value = -9.337, sig value (2-tailed) = 0.001 <0.05. It means that the use of the PjBL method can improve student learning outcomes in descriptive writing learning. Based on the results of questionnaire analysis concerning the students’ perceptions of the implementation of the PjBL method in learning descriptive writing, the indicator of lecturer and student interaction was the highest with the